РОЗВИТОК ЕСТЕТИЧНИХ ПОЧУТТІВ МАЙБУТНІХ ВЧИТЕЛІВ ТЕХНОЛОГІЇ (Педагогіка вищої та середньої школи, 2008)
In this article і analyse the importance of developing of esthetic feelings. The meaning of developing of esthetic feeling for the social activity of future teacher is opening.